Cash flows: The Gap Between Reported and Estimated Operating Cash Flow Elements - M. Hughes; S. Hoy; B. Andrew (Australasian Accounting, Business and Finance Journal, 2010)
The FASB and the IASB recently released a joint Discussion Paper “Preliminary Views on Financial Statement Presentation” (International Accounting Standards Board 2008), which contains a major proposal requiring companies to report operating cash flows using the direct method and it also requires that the indirect method of calculating operating cash flows be disclosed in the notes. This is a departure from current rules and has generated considerable debate among respondents’ comment letters on the Discussion Paper. This paper adds to this debate by providing some evidence as to the size of the gap users confront when using the indirect method to estimate the major operating cash flow elements, such as cash collected from customers and cash paid to suppliers. Using a sample of Australian companies which reported operating cash flows using the direct method, and presented the indirect method in the notes, we find significant differences between reported and estimated figures for both cash collected from customers and cash paid to suppliers. These findings support the discussion paper’s proposal that companies be required to report cash flows using both the direct and indirect methods.